Contact Aspiration Versus Stent Retriever in Patients With Acute Ischemic Stroke With M2 Occlusion in the ASTER Randomized Trial (Contact Aspiration Versus Stent Retriever for Successful Revascularization). Issue 2 (February 2018) - Gory, Benjamin; Lapergue, Bertrand; Blanc, Raphael; Labreuche, Julien; Ben Machaa, Malek; Duhamel, Alain; Marnat, Gautier; Saleme, Suzana; Costalat, Vincent; Bracard, Serge; Desal, Hubert; Mazighi, Mikael; et al.
Abstract : Background and Purpose—: Middle cerebral artery M2-segment occlusions represent an important subgroup of patients with acute stroke with large-vessel occlusion. The safety of mechanical thrombectomy, especially contact aspiration (CA), in such distal intracranial occlusions is still under debate. We compared reperfusion, adverse events, neurological recovery, and functional outcome of patients with isolated M2 occlusions according to the first-line strategy mechanical thrombectomy devices (CA versus stent retriever [SR]). Methods—: This is a post hoc analysis of the ASTER trial (Contact Aspiration Versus Stent Retriever for Successful Revascularization). The primary outcome was successful reperfusion at the end of all endovascular procedures, defined as modified Thrombolysis in Cerebral Infarction (mTICI) scores 2b/3. Secondary outcomes were mTICI 2c/3 and mTICI 3, 90-day functional outcome, assessed with the modified Rankin Scale score. Safety outcomes included 90-day mortality and any symptomatic intracerebral hemorrhage. Results—: Seventy-nine patients were included: 48 were allocated to the CA group and 31 to the SR group. There were no significant differences between CA and SR groups in reperfusion after all endovascular procedures regarding mTICI 2b/3 (89.6% versus 83.9%; P =0.36), mTICI 2c/3 (54.2% versus 54.8%; P =0.90), and mTICI 3 (35.4% versus 41.9%; P =0.36) rates. There were no significant differences between CA and SR groups in 90-day modified Rankin Scale ⩽2 rate (54.4% versus 50.0%; P =0.84), 24-hour change in National Institutes of Health Stroke Scale (mean difference, −3.9; 95% confidence interval, −7.9 to 0.01), and Alberta Stroke Program Early Computed Tomography score (mean difference, 0.9; 95% confidence interval, −0.1 to 2.0) scores. Safety parameters were well balanced between the 2 groups except for a higher 90-day mortality rate in the CA group (19.6% versus 3.3%; P =0.078). Conclusions—: First-line mechanical thrombectomy with CA compared with SR did not result in an increased successful revascularization rate in patients with acute stroke with isolated M2 occlusion. Abstract : Supplemental Digital Content is available in the text.